New specimens of the rare taeniodont Wortmania (Mammalia: Eutheria) from the San Juan Basin of New Mexico and comments on the phylogeny and functional morphology of "archaic" mammals. - Thomas E Williamson (Public Library of Science (PLoS), 2013)
Background Taeniodonta is a clade of Late Cretaceous-Paleogene mammals remarkable for their relatively extreme cranial, dental, and postcranial adaptations and notable for being among the first mammals to achieve relatively large size following the Cretaceous-Paleogene mass extinction. Previous workers have hypothesized that taeniodonts can be divided into two clades: Conoryctidae, a group of small-bodied taeniodonts with supposedly "generalized" postcranial skeletons, and Stylinodontidae, a group of large-bodied, robust animals with massive forelimbs and claws adapted for scratch-digging. However, many taeniodont taxa are poorly known and few are represented by postcranial material, leaving many details about their anatomy, biology, and evolution ambiguous. Methodology/principal findings In this paper, we describe three new specimens of the rare taxon Wortmania otariidens from the early Paleocene (Puercan) of New Mexico. Among these specimens is one that includes remarkably complete cranial and dental material, including associated upper and lower teeth, and another that consists of partial forelimbs. These specimens allow for an updated anatomical description of this unusual taxon, supply new data for phylogenetic analyses, and enable a more constrained discussion of taeniodont biology and functional morphology. Conclusions/significance The new specimen of Wortmania that includes associated upper and lower teeth indicates that previous interpretations of the upper dentition of this taxon were not accurate and the taxon Robertschochia sullivani is a junior synonym of W. otariidens. New specimens that include partial forelimbs indicate that Wortmania is very similar to later, large-bodied taeniodonts, with marked and distinctive adaptations for scratch-digging. Comparisons with other taeniodont taxa that include postcranial material suggest that all taeniodonts may have had scratch-digging adaptations. A phylogenetic analysis shows that Schowalteria and Onychodectes are basal taeniodonts, Stylinodontidae (including Wortmania) is monophyletic, and a monophyletic Conoryctidae (but not including Onychodectes) is only recovered when certain characters are ordered.